Early Yield Testing and Selection of Upland Rice on Observational Study in Kebumen, Central Java - Angelita Puji Lestari; Aris Hairmansis; Rini Hermanasari; Yullianida Yullianida; Suwarno Suwarno (Breeding Science Society of Indonesia (BSSI) / PERIPI, 2019)
The use of upland rice variety is an effort to expand rice cultivation to dry land due to the decreasing of fertile land in Indonesia. To develop a high yielding rice line, a primary population with high genetic diversity is needed in character related to grain yield. This experiment aimed to study the genetic variability of some important characters of upland rice lines as primary data for the selected program. The research was carried out in the farmland of Mirit Village, Kebumen, Central Java. The genetic material consisted of 203 new promising lines and five varieties as a check, namely Inpago 6, Inpago 8, Limboto, Situpatenggang, and Situbagendit. This observation yield trial used an augmented design with five replicates of the check varieties, with a spacing of 30 x 15 cm. The data analysis showed that the rice lines, line vs. check, and block were significantly different in the number of productive tillers. The significant effects of lines with the check varieties were in plant height, flowering age, harvest age, and a number of productive tillers. The number of productive tillers had wide genetic variation, broad-sense heritability, and high genetic gain so that it can be utilized as selection criteria. Twelve lines were identified as a higher number of productive tillers, and three lines had a higher yield compared to the best varieties of Situbagendit.